Digital assessment of properties of the three different generations of dental elastomeric impression materials - Lamia Singer; Shaymaa I. Habib; Heba El-Amin Shalaby; Sayed H. Saniour; Christoph Bourauel (BMC, 2022)
Abstract Background This study aimed to compare the dimensional accuracy, hydrophilicity and detail reproduction of the hybrid vinylsiloxnether with polyether and polyvinylsiloxane parent elastomers using modified digital techniques and software. This was done in an attempt to aid in solving the conflict between the different studies published by competitive manufacturers using different common manual approaches. Methods A polyether, polyvinylsiloxanes and vinyl polyether silicone hybrid elastomeric impression materials were used in the study. Dimensional accuracy was evaluated through taking impressions of a metallic mold with four posts representing a partially edentulous maxillary arch, that were then poured with stone. Accuracy was calculated from the mean of measurements taken between fixed points on the casts using digital single-lens reflex camera to produce high-resolution digital pictures for all the casts with magnification up to 35×. Hydrophilicity was assessed by contact angle measurements using AutoCAD software. The detail reproduction was measured under dry conditions according to ANSI/ADA Standard No. 19 and under wet conditions as per ISO 4823. A metallic mold was used with three V shaped grooves of 20, 50, and 75 µm width. Specimens were prepared and examination was made immediately after setting using digital images at a magnification of 16×. Results The hybrid impression (0.035 mm) material showed significantly higher dimensional accuracy compared to the polyether (0.051 mm) but was not as accurate as the polyvinyl siloxane impression material (0.024 mm). The contact angles of the hybrid material before and after setting was significantly lower than the parent materials. With regard to the detail reproduction, the three tested materials were able precisely to reproduce the three grooves of the mold under dry conditions. Whereas, under wet conditions, the hybrid material showed higher prevalence of well-defined reproduction of details same as polyether but higher than polyvinylsiloxane that showed prevalence of details with loss of sharpness and continuity. Conclusions The digital technique used could be a more reliable and an easier method for assessment of impression materials properties. The hybridization of polyvinyl siloxane and polyether yielded a promising material that combines the good merits of both materials and overcomes some of their drawbacks.